Measuring the surface temperature of light-emitting diodes by thermoreflectance. (5th May 2021) - Zheng, Dong-Guang; Shin, Dong-Soo; Shim, Jong-In
Abstract: As the latest applications of LEDs require more harsh operating conditions, understanding the device thermal properties becomes more essential for further improving the device efficiencies. In applications where heat dissipation can be a critical issue, thermoreflectance (TR) can be utilized as a useful noncontact measurement technique for analyzing the thermal properties. In this paper, we investigate the TR method of measuring the surface temperature, using a lateral-type blue LED chip under high-power operation. The TR we employ measures the change in reflectivity from the Au metal electrode. By comparing with surface/junction temperatures measured by other methods based on the thermocouple and the forward voltage, we find that the TR method can provide accurate and reliable results of measuring the surface temperature of modern LEDs. A useful insight can also be obtained from the temperature distribution on the LED chip surface.